2015
DOI: 10.1038/srep09216
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of Gram-negative bacteria to rifampin and OAK combinations

Abstract: While individually inefficient against Gram-negative bacteria, in-vitro combinations of rifampin and OAK were mutually synergistic since sub-minimal inhibitory concentrations of one compound have potentiated the other by 2–4 orders of magnitude. Synergy persisted in-vivo as single-dose systemic treatment of Klebsiella infected mice resulted in 10–20% versus 60% survival, respectively accomplished by individual and combined compounds. This outcome was achieved without drug formulation, rather, pharmacokinetic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 47 publications
6
51
0
Order By: Relevance
“…In summary, while C 10 OOc 12 O was previously proposed to sensitize GNB to host plasma antibacterial proteins (29), the present study provides evidence for the MAC's capacity to perform much better in the presence of an antibiotic, bestowing potent antibacterial activity onto virtually inactive endogenous and/or exogenous compounds. In this sense, the current work ratifies the conclusions drawn in previous studies (20,28,29) that propose that the newly found antibacterial potencies are likely to stem from the damaged OM and/or CM, thereby supporting this approach's potential usefulness in the search of new alternatives to antibiotics.…”
Section: Enhancing In Vivo Efficacies Through Combination Therapiessupporting
confidence: 84%
See 1 more Smart Citation
“…In summary, while C 10 OOc 12 O was previously proposed to sensitize GNB to host plasma antibacterial proteins (29), the present study provides evidence for the MAC's capacity to perform much better in the presence of an antibiotic, bestowing potent antibacterial activity onto virtually inactive endogenous and/or exogenous compounds. In this sense, the current work ratifies the conclusions drawn in previous studies (20,28,29) that propose that the newly found antibacterial potencies are likely to stem from the damaged OM and/or CM, thereby supporting this approach's potential usefulness in the search of new alternatives to antibiotics.…”
Section: Enhancing In Vivo Efficacies Through Combination Therapiessupporting
confidence: 84%
“…However, data shown in Fig. 2B, as well as results from previous studies (18,28), argue against such a possibility. In fact, even less hydrophobic analogs (e.g., C 8 KKc 12 K) were able to damage the OM.…”
Section: Evidence For Membrane Damagementioning
confidence: 56%
“…3). Under similar conditions 46 the analogs C 8 , C 10 and C 12 exhibited a binding affinity that was lower than that of C 14 KKc 12 K but increased with increasing hydrophobicity 40 . This is further addressed below.
Figure 3Dansyl-polymyxin binding assay.
…”
Section: Resultsmentioning
confidence: 97%
“…The synergism may result from complement proteins and/or clotting factors [60]. Further, a single combined dose of oligo-acyl-lysyls (OAKs) with rifampin also imparts increased survival chances from 10–20% to 60% against Klebsiella infected mice [61]. In addition, the combination of a lipopeptide bacillomycin D with antifungal amphotericin B leads to excellent antibiofilm and wound-healing properties against Candida albicans [62].…”
Section: Application Strategies Of Antimicrobial Peptidesmentioning
confidence: 99%